RIZATRIPTAN BENZOATE LOADED NATURAL POLYSACCHARIDE BASED MICROSPHERES FOR NASAL DRUG DELIVERY SYSTEM - Sharma, Meenakshi; Sharma, Nitin; Sharma, Anjana (International Journal of Applied Pharmaceutics, 2018)
Objective: The objective of this research was to formulate and evaluate the different grades of rizatriptan benzoate loaded polysaccharide based microspheres for the nasal drug delivery system. Methods: The polysaccharide was extracted from the seed of Trigonella foenum-graecum and microspheres were prepared by emulsification, followed by crosslinking using epichlorohydrin. A 32 full factorial design was employed in formulating the microspheres with polymer concentration (X1), and stirring rate (X2) as independent variables and particle size (Y1) and entrapment efficiency (Y2) were dependent variables. Results: The microspheres were discrete and free-flowing. The mean particle size (Y1) of microspheres ranged from 40.82+12 µm to 62.48+0.41 µm and the encapsulation efficiency (Y2) was found to be increased from 60.7+0.2% to 79.22+0.2% as the drug polysaccharide ratio increased. A 32 full factorial design confirmed that the X1 and X2 both effect on particle size whereas X1 alone effect on entrapment efficiency. SEM revealed the smooth spherical surface of microspheres whereas kinetic model revealed that drug release followed the case II transport. FTIR indicated good compatibility of the excipients with rizatriptan benzoate. Stability studies were carried out for formulation F7 at 4°C ambient, 25+2°C/60+5%, 40+2°C/75+5% relative humidity revealed that the physical drug appearance, entrapment efficiency were within the permissible limits. Conclusion: The result obtained in this research work indicate a promising potential of control release rizatriptan benzoate loaded microspheres whereas the Trigonella foenum-graecum polysaccharide used as rate controlling polymer for the effective treatment of migraine patients.